Novel Oxovanadium Complex VO(hntdtsc)(NPIP): Anticancer Activity and Mechanism of Action on HeLa Cells - Bai, Yinliang; Zhang, Honghua; Wang, Yali; Zhu, Longqing; Shi, Tao; Wei, Hangzhi; Xiao, Jiyuan; Zhang, Youcheng; Wang, Zhen (Frontiers in Pharmacology, 2021)
Oxovanadium complexes, particularly vanadyl (IV) derivatives with hybrid ligands of Schiff base and polypyridyl have been demonstrated to possess great therapeutic efficacy in anticancer. However, most of the studies on the activity of these oxovanadium complexes have mainly focused on in vitro studies, animal studies in vivo are extremely scarce. Based on the antitumor test results of four novel oxovanadium complexes in our previous work, this work further conducted a comprehensive anti-tumor activity study in vitro and in vivo on VO(hntdtsc)(NPIP), which owned the strongest inhibitory activity in vitro on multiple tumor cell proliferation. The cellular mechanism study suggested that VO(hntdtsc)(NPIP)inhibited the cell proliferation via arresting the cell cycle at G0/G1 phase through the p16-cyclin D1-CDK4-p-Rb pathway and inducing cell apoptosis through mitochondrial-dependent apoptosis pathway on HeLa cells. In consistent with the effects in vitro, VO(hntdtsc)(NPIP) significantly inhibited the growth of tumor and induced the apoptosis of cancer cells in mice xenograft models according to the results of nude mice in vivo image detection, H&E pathological examination and immunohistochemical detection of p16/Ki-67 protein expression, etc. Collectively, all the results, particularly studies in vivo demonstrated that VO(hntdtsc)(NPIP) hold a potential to be the lead compound and further to be an anti-cervical cancer drug.